2020
DOI: 10.3390/molecules25051073
|View full text |Cite
|
Sign up to set email alerts
|

Activation of JNK and p38 in MCF-7 Cells and the In Vitro Anticancer Activity of Alnus hirsuta Extract

Abstract: JNK and p38 are important mitogen-activated protein kinases (MAPKs) that respond to stress stimuli. The stress-activated MAPKs associated with apoptotic cell death play vital roles in mammalian cells. Alnus hirsuta, which contains abundant diarylheptanoids derivatives, is a valuable medicinal plant. The CHCl3 extract (AHC) containing platyphyllenone (1) and platyphyllone (3) as main compounds showed in vitro anticancer effects. We report the biological activities of A. hirsuta extract associated with the regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 70 publications
2
21
0
Order By: Relevance
“…It is known that JNK, ERK and p38 are all members of the MAPK pathway which are involved in cell proliferation, differentiation, cell cycle and apoptosis ( 25 ). Numerous anticancer drugs exert their effects through the p38 MAPK or ERK/MAPK signaling pathways to control cell proliferation ( 23 , 25 , 26 , 36 ). c-JUN is the major downstream target of JNK signaling, and transcriptional regulation of c-JUN and its target genes is one of the main functions of JNK ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that JNK, ERK and p38 are all members of the MAPK pathway which are involved in cell proliferation, differentiation, cell cycle and apoptosis ( 25 ). Numerous anticancer drugs exert their effects through the p38 MAPK or ERK/MAPK signaling pathways to control cell proliferation ( 23 , 25 , 26 , 36 ). c-JUN is the major downstream target of JNK signaling, and transcriptional regulation of c-JUN and its target genes is one of the main functions of JNK ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different members of the CDK family are associated with different cyclins, which play an important role in switching from one phase to the next throughout the cell cycle ( 22 ). Numerous anticancer drugs induce cell cycle arrest to inhibit tumor cell proliferation ( 23 26 ). Studies have revealed that garcinol can also induce cell cycle arrest to inhibit cell growth in lung cancer ( 26 ), cervical ( 19 ), oral ( 24 ), and breast cancer ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…There was a significant increase in protein content of LETW compared to the peptides-enriched fraction of wild-type wheat (PEWW), and the increasing trend was positively correlated with the concentration of LETW ( Figure 3 c). Using ELISA to engage at least one antibody with an exclusive counterpart antigen is an approach used to improve sensitivity and specificity [ 26 ]. Subsequently, the lunasin content of LETW was measured via a modified ELISA method.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is not easy to express an exogenous gene into hexaploid wheat due to the lower transformation efficiency. Hence, in order to address this limitation, we constructed the expression vector without unnecessary vector backbone DNA in early generations, according to the research of Wang et al [ 28 ], and we decreased the bar gene integration by changing the sizes of the two independent T-DNA regions in the vector [ 26 ]. Then, the transgenic wheat lines were generated by the Agrobacterium -mediated co-transformation method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation